Efektivitas Dana Zakat Dalam Pengembangan Dan Pemberdayaan Ekonomi Mustahik di Kalangan UMKM Pada Badan Amil Zakat Nasional (BAZNAS) Provinsi Sumatera Utara - Husdiana Husdiana; Imsar Imsar (Universitas Muhammadiyah Metro, 2023)
This research is a research conducted with the aim of knowing how the effectiveness of zakat funds in developing and empowering the mustahik economy among MSMEs in the National Amil Zakat Agency (Baznas) of North Sumatra Province and How is the distribution of the zakat funds done. The research method used is descriptive qualitative method using primary data sources. Data collection techniques used through observation, interviews and documentation. In addition, this study also uses secondary data sources obtained through articles or online or through the North Sumatra Baznas website. The results showed that zakat funds in developing and empowering the mustahik economy among MSMEs at the Baznas of North Sumatra Province were quite effective. Because the existence of zakat funds is able to help SMEs in developing and activating their economy. Although the hope of Baznas is to turn MSME actors who were previously mustahik into muzakki, this zakat fund is quite capable and effective in assisting MSME actors in developing and empowering the economy in their lives and increase monthly income.